The Lawyer as Process and Project Manager for Infrastructure Projects - Roth, Maximilian (Studia Prawa Publicznego, 2025)
In the Federal Republic of Germany, lawyers can be employed as project managers to relieve the authorities of the burden of approval procedures for large infrastructure projects. This particularly applies to procedures for the expansion of federal highways, railway lines or trams, power lines or wind turbines. This article presents the relevant legal basis, classifies it in relation to the state, and highlights the opportunities and risks of employing a lawyer as a project manager: The lawyer has a secure and large mandate for a longer period of time and can rely on a secure fee due to the solvency of the state. For the project sponsor, the use of a project manager means that the procedure can be completed more quickly, and external expertise or know-how represents additional support for the authority, which in principle cannot be detrimental. The cooperation between project manager and authority can take place under civil law on the basis of a contract or under public law via a public-law contract, in accordance with the provisions of the Administrative Procedure Act. The article concludes with a conclusion and summarizes the main findings.